Spatial distribution of bovine cysticercosis—A retrospective study in Brazil from 2010 through 2015 - Rossi, Gabriel Augusto Marques [UNESP] (2017)
Geographical Information Systems (GIS) is frequently used in the control of animal diseases. In Brazil, the most impacting economical loss in the beef supply chain is bovine cysticercosis. This study focused on assessing the prevalence and geospatial distribution of bovine cysticercosis in 19 Brazilian states. To this, we gathered data from 146,346,244 bovines slaughtered between the years of 2010 and 2015. The observed prevalence was 0.62% (C.I. 0.62–0.63). In total, 30.86% cysticerci were viable, while 69.14% were unviable. Bovine cysticercosis cases had a significant decrease (p < 0.05) during this period. The states of Paraná (2.01%; C.I. 2.00–2.02), Santa Catarina (1.96%; C.I. 1.93–2.00), São Paulo (1.77%; C.I. 1.76–1.77), Rio Grande do Sul (1.63%; C.I. 1.60–1.63) and Mato Grosso do Sul (0.80%; C.I. 0.80–0.80) had the highest prevalence values. In some states a significant (p < 0.05) decreasing trend was detected in the prevalence. In conclusion, Taenia-saginata-cysticercosis remains endemic in Brazil and interventions are necessary to maintain Brazilian beef competitive in the international food market and improve food safety to population.